New record of the genus Isonychia (Ephemeroptera: Isonychiidae) in Mexico and water parameters data - Rodríguez-Ríos, Edwin Alán; Cardoza Martínez, Gabriel Fernando; Alonzo Rojo, Fernando; Valenzuela García, Ana Alejandra; Álvarez-Zagoya, Rebeca; Estrada Arellano, Josué Raymundo (Ecosistemas y Recursos Agropecuarios, 2024)
The genus Isonychia groups mayflies with large nymphs present in lotic ecosystems. This genus has a very wide distribution, despite of this, in Mexico the records are very scarce and these do not refer to the environmental characteristics of the sites where they were found. The objective of this work is to report for the first time the genus Isonychia in Durango state, as well as to characterize some physicochemical parameters of water associated with its distribution. A total of 19 Isonychia nymphs, which probably correspond to the species I. sicca, were recorded in seven sites within the Nazas River basin. This extends the distribution range of the genus Isonychia for Mexico. The specimens were recorded in environments with moderate current speed and an acceptable water quality compared to other riparian systems, in terms of dissolved oxygen, electrical conductivity, total dissolved solids, pH, temperature and ammonium.